(untitled) (Journal of Solar Energy Research Updates, 2021)
Solar energy utilization is vital for our society which faces the global warming problem and the increase in the prize of fossil fuels. Concentrating solar collectors are a promising technology for producing useful energy from the sun. In this study, an innovative concentrating collector with a paraboloid dish reflector is presented and simulated. The main idea of this collector is the use of a dish reflector for continuous heat production with a high concentration ratio. For this reason, a spherical receiver absorber with two linear insulated ducts is used. The cost of this system is relative low because there is not a glass cover but a tracking system is required. The final results show better performance than the typical collectors such as the flat plate collectors and the evacuated tube collectors, fact that makes this collector a promising solution. The design and the simulation are carried out with the commercial software Solidworks, in the flow simulation studio.